2006
DOI: 10.1103/physrevlett.97.242503
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Cascade Transition via the First Excited State ofO16in theC12et al.

Abstract: Radiative alpha-particle capture into the first excited, J(pi)=0+ state of 16O at 6.049 MeV excitation energy has rarely been discussed as contributing to the 12C(alpha,gamma)16O reaction cross section due to experimental difficulties in observing this transition. We report here measurements of this radiative capture in 12C(alpha,gamma)16O for center-of-mass energies of E=2.22 MeV to 5.42 MeV at the DRAGON recoil separator. To determine cross sections, the acceptance of the recoil separator has been simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 11 publications
2
56
1
Order By: Relevance
“…The sub-Coulomb transfer reaction experiment of Avila et al (2015) has reconfirmed the earlier measurements of the α ANCs for the levels at E x = 6.92 (2 + ) and 7.12 (1 − ) MeV and has additionally measured those of the E x = 6.05 (0 + ) and 6.13 (3 − ) MeV states for the first time. These measurements reconfirmed the assertion of Schürmann et al (2011) that the large value for the low energy S-factor of the E x = 6.05 MeV transition given in Matei et al (2006) was incorrect. However, the value found in Avila et al (2015) is also in disagreement with that of Schürmann et al (2011) since their assumed ANC was significantly smaller than that measured by Avila et al (2015).…”
Section: Return To Indirect Techniques ('93-present)supporting
confidence: 70%
See 4 more Smart Citations
“…The sub-Coulomb transfer reaction experiment of Avila et al (2015) has reconfirmed the earlier measurements of the α ANCs for the levels at E x = 6.92 (2 + ) and 7.12 (1 − ) MeV and has additionally measured those of the E x = 6.05 (0 + ) and 6.13 (3 − ) MeV states for the first time. These measurements reconfirmed the assertion of Schürmann et al (2011) that the large value for the low energy S-factor of the E x = 6.05 MeV transition given in Matei et al (2006) was incorrect. However, the value found in Avila et al (2015) is also in disagreement with that of Schürmann et al (2011) since their assumed ANC was significantly smaller than that measured by Avila et al (2015).…”
Section: Return To Indirect Techniques ('93-present)supporting
confidence: 70%
“…Further, in that work an R-matrix fit was made to this data that gave a much larger low energy contribution than previously estimated. A subsequent measurement by Schürmann et al (2011) over a more limited higher energy range claimed that their data was inconsistent with that of Matei et al (2006) and their R-matrix fit predicted the opposite extreme, that the transition's contribution was lower than previously estimated. A reanalysis of the data of Schürmann et al (2011) by deBoer et al (2013 found a value in between the two, which was closer to previous estimates.…”
Section: Cascade Transitionsmentioning
confidence: 86%
See 3 more Smart Citations